Depoliticize Human Immunodeficiency Virus Infection: A Commentary - Marvin S. Amstey (Hindawi Limited, 1994)
Public-health policy is inconsistent in its approach to the sexually transmitted disease human immunodeficiency virus (HIV). Nearly every health agency has politicized the reporting, finding, and contacting of HIV cases. There is also no consistency among the various state health departments and the various federal health agencies. Until we have a uniform health policy that treats HIV infection as every other reportable sexually transmitted disease, we will make little progress toward controlling its inevitable increase in both cases and costs.